ANALISIS ABRASI DAN AKRESI PERAIRAN PANTAI BARUS TAPANULI TENGAH DENGAN MODEL CEDAS 2.0 - Novi Andhi Setyo Purwono (Jurnal Teknik Sipil, 2021)
Barus is an area where most of the people are fishermen, this is because Barus is an area located on the coast. The existing condition shows the shoreline on the east side of the seawall building, the condition of the shoreline is experiencing abrasion resulting in the retreat of the coastline and almost reaches the fisherman's flat building area, this is due to the port building in the form of a massive trester jutting into the sea resulting in sediment supply to the retained flat towers and the coastline has declined.To maintain the stability of the coastline, it is necessary to make an effort to control the damage to water in this area. The shoreline model is a numerical forecast model based on the sediment continuity equation and the sediment transport rate equation along the coast. Sediment transport rates along the coast are a function of the variation in height and direction of waves along the coast formed by the effects of refraction and diffraction. The results of the shoreline change model with the protection of the fisherman's flat area from waves by building sea walls is the east side of the fisherman's towers abrasion ± 7 m and sedimentation ± 5 m, the front area of the fisherman's towers does not occur sedimentation or abrasion, the western side of the fisherman's towers does not sedimentation and abrasion occurred, the east side of Barus Jetty did not occur abrasion or sedimentation, the area of Barus Jetty occurred ± 20 m sedimentation, and the west side of Barus Jetty occurred sedimentation ± 9 m. These results indicate that for handling conditions by making a seawall in front of the flat area shows that the location is safe from scouring of waves